Faktor-Faktor Yang Mempengaruhi Kualitas Laporan Keuangan Pemerintah Daerah: Studi Kasus Pada Pemerintah Daerah Kabupaten Sleman D.I Yogyakarta - Marlela Wati; Fajar Satriya Segarawasesa (CV. Ulil Albab Corp, 2023)
This study aims to analyze the effect of the Regional Financial Accounting System, Utilization of Information Technology, Human Resource Competence, and Internal Control System on the quality of the local government's financial statements in Sleman Regency. This research was quantitative research. The population of this research was structural officials at the Regional Government Work Unit of Sleman Regency, DIY. The sampling was done by employing purposive sampling. Data collection was carried out by distributing questionnaires to the Regional Government Work Unit employees of Sleman Regency. The data that has been collected was processed using SPSS 20. The statistical method used to test the hypothesis was multiple linear regression analysis. The results of hypothesis testing indicate that the Regional Financial Accounting System and Utilization of Information Technology have a positive effect on the quality of local government financial reports, while Human Resource Competence and Internal Control Systems have no effect on the quality of local government financial reports.